Comment on Casimir force in compact non-commutative extra dimensions and radius stabilization - De Albuquerque, Luiz C. [UNESP]; Cavalcanti, R. M. (Int School Advanced Studies, 2001)
We call attention to a series of mistakes in a paper by S. Nam recently published in this journal (J. High Energy Phys. 10 (2000) 044).
Keywords: field theories in higher dimensions; non-commutative geometry